Profile of orthodontic services provided in private practice by general practitioners and specialist orthodontists for an insured population - Sivaneswaran Shanti; Ali Darendeliler M. (Sciendo, 2001)
In Australia, the proportion, volume and type of orthodontic care provided by general practitioners and orthodontists are largely unknown. The overall objective of this study was to create a profile of orthodontic services provided by general practitioners and orthodontists for a cohort of insured patients using private practices in New South Wales, Australia, from 1st January 1992 to 31st December 1995. Data were derived from claims records submitted by members of a health insurance fund for rebates for fees paid to private practitioners for orthodontic services they received during the study period. Distribution of the volume and type of service provided by general practitioners and orthodontists was compared using the Chi-squared test. Statistical significance was taken at the 5 per cent level. Orthodontic services were provided predominantly by orthodontists (80%). Fixed orthodontic treatment was provided almost exclusively (91%) by orthodontists. The majority of removable appliance services was provided by general practitioners. Orthodontists provided more orthodontic services in the capital city and other metropolitan areas, whereas general practitioners provided more orthodontic services in rural areas. Orthodontists provided more services to members in the highest socio-economic group, whereas general practitioners provided more services to members in the lowest socioeconomic group.